The Effect of Competence and Job Satisfaction on Employee Loyalty in the Cement Industry - Bakti Setyadi; Dewi Sartika; Sulaiman Helmi (PT Mattawang Mediatama Solution, 2023)
This study aims to examine the effect of competence (Competence) and job satisfaction (Job Satisfaction) on employee loyalty at PT Semen Baturaja Palembang. The research method used was a survey with a cross-sectional design, and the sample consisted of 98 employees selected using convenience sampling. Data were collected through a questionnaire with a Likert scale of 1 to 5, which had gone through a validity and reliability assessment. Data analysis was conducted using multiple linear regression with Smart PLS application. The results of the analysis show that competence and job satisfaction have a positive and significant effect on employee loyalty. Competence and job satisfaction can explain about 59.8% of the variation in employee loyalty. The recommendations proposed are that companies need to improve employee competencies through relevant training and development and pay attention to other factors that affect loyalty. In addition, it is important to continuously monitor and improve employee job satisfaction levels and conduct periodic evaluations to create a productive and competitive work environment. The implementation of these recommendations is expected to strengthen employee engagement, improve retention, and create a work environment that contributes to the overall success of the organization.